Isoenzymes of the Glycolytic and Pentose Phosphate Pathways in Proplastids from the Developing Endosperm of Ricinis communis L. - Simcox, P. David (1978)
Two isoenzymes each of hexose-P isomerase, aldolase and 6-P-gluconate dehydrogenase have been found in the endosperm of developing castor beans (Ricinus communis L.). One isoenzyme for each activity is present in the proplastid fraction. Only one form of glucose-6-P dehydrogenase was found. It is suggested that the partition of an enzyme activity between cytosol and plastid is regulated by the synthesis of isoenzymes which are subcellular site specific. In addition, this report describes the use of diethylaminoethyl-Sephadex A-25 sievorptive chromatography for the preparation of plant enzymes.